2002
DOI: 10.1097/01.asn.0000026609.45827.3d
|View full text |Cite
|
Sign up to set email alerts
|

Postischemic Acute Renal Failure Is Reduced by Short-Term Statin Treatment in a Rat Model

Abstract: Abstract. Postischemic acute renal failure (ARF) is common and often fatal. Cellular mechanisms include cell adhesion, cell infiltration and generation of oxygen free radicals, and inflammatory cytokine production. Hydroxy-3-methylglutaryl coenzyme A reductase inhibitors ("statins") directly influence inflammatory mechanisms. The hypothesis that ischemiainduced ARF could be ameliorated with statin treatment was investigated and possible molecular mechanisms were analyzed in a uninephrectomized rat model. Male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
92
1
6

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(105 citation statements)
references
References 33 publications
6
92
1
6
Order By: Relevance
“…On the third day, both mice were subjected to bilateral renal I/R injury. Consistent with the results of previous studies, 14,15 treatment with fluvastatin ameliorated renal I/R injury in control mice, as assessed by serum levels of urea nitrogen and creatinine, histologic analyses, and expression of cell adhesion molecules ( Figure 6). However, of importance, fluvastatin did not attenuate renal I/R injury in Klf4 cKO mice.…”
Section: Inflammatory Cell Accumulation and Expression Of Cell Adhesionsupporting
confidence: 91%
See 2 more Smart Citations
“…On the third day, both mice were subjected to bilateral renal I/R injury. Consistent with the results of previous studies, 14,15 treatment with fluvastatin ameliorated renal I/R injury in control mice, as assessed by serum levels of urea nitrogen and creatinine, histologic analyses, and expression of cell adhesion molecules ( Figure 6). However, of importance, fluvastatin did not attenuate renal I/R injury in Klf4 cKO mice.…”
Section: Inflammatory Cell Accumulation and Expression Of Cell Adhesionsupporting
confidence: 91%
“…To address this question, we derived conditional Klf4-deficient mice in ECs (Klf4 cKO mice) by breeding Tek-Cre mice 12 with mice carrying a loxP allele of Klf4 (Klf4 loxP mice) 13 and analyzed their phenotype after bilateral renal ischemia. In addition, statins, 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitors, have been shown to improve ischemic AKI in rodents 14,15 and humans. 16,17 For example, pretreatment with cerivastatin for 3 days reduced renal I/R injury by preventing inflammatory cell infiltration and by inhibiting Icam1 induction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[33][34][35][36][47][48][49] These differences may derive from the diversity of the mechanisms of each model or duration of the drug administration. In addition, many studies with streptozotocin-induced diabetic animals were performed for a relatively short duration compared to chronic diabetes in human.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Only recently have studies demonstrated the significance of FGF23 in mineral metabolism in the larger population of patients with CKD and ESRD. [5][6][7] In 2007, Fliser et al 8 reported that higher FGF23 levels were strongly associated with progression of non diabetic CKD. The next year, Gutierrez et al 9 published that incident hemodialysis patients with higher FGF23 levels were at substantially greater risk for allcause mortality.…”
Section: New Insights To Fibroblast Growth Factor 23 In Kidney Transpmentioning
confidence: 99%